A Scalable Telegram-Based Botnet Framework for Stealthy Remote Command and Control - Toi, Pham Van; Dung, Nguyen Trung; Phương, Hoang Linh; Long, Nguyen Huu (Journal of Science and Technology on Information security, 2025)
In this study, we analyze how Telegram Bots can be abused as a Command and Control (C2) infrastructure in cyberattacks. We propose a Telegram-based C2 model that enables attackers to control compromised systems without relying on a centralized server, thereby enhancing anonymity and evasion capabilities. Furthermore, we introduce detection and defense strategies based on network behavior monitoring and encrypted message analysis.